Brand Avoidance Behavior in Sustainable Fashion: Insights from Generation Z Consumers - Yeshika Alversia; Natasha Syifa Hakeki (Journal of Research in Social Science and Humanities, 2025)
This study aims to determine the factors that influence brand avoidance behavior in the purchase of sustainable fashion products by Generation Z in Jabodetabek. The samples used in this study were men and women with an age range of 18-26 years, domiciled in the areas of Jakarta, Bogor, Depok, Tangerang, Bekasi and had transacted or purchased fashion products. There were 236 respondents collected using a purposive sampling method. Then processed and analyzed using Partial Least Square - Structural Equation Method (PLS-SEM). This study found that sustainable fashion avoidance intention, which is influenced by ideological incompatibility, unmet expectations, and materialism, positively and significantly influences sustainable fashion avoidance behavior by Generation Z in Jabodetabek.